Troubled orthodontic patients: the role of the social worker - Wright Janice L.; Jacobs Stanley G. (Sciendo, 1990)
Cooperation and social problems of orthodontic patients. are discussed using four case histories, and the significant role of the social worker in managing such patients is explained.